The influence of transmission system disturbances on the dynamic behaviour of a wind park - Castro, Rui (2013)
In this paper an integrated non-linear model of both the wind park and the interconnecction network is presented. The model is an integartion of model previously developed for each componenet of the system, namely wind turbines, induction generators, reactive power compensation system, transformers, feeder and possible local loads connected to the feeder. In order to draw some conclusions regarding the interaction between wind parks and the existing a.c. system, some case studies have been performed using the developed models.